(Re)conceptualising Reconciliation: Transitional Justice in Sri Lanka - Xavier, Sujith (Groundviews, 2016)
Featured image courtesy Sydesian Transitional justice is a popular term in present day Sri Lanka. It is the means by which the various parties to the conflict have decided to bring about justice an…
Keywords: Sujith Xavier